Busting Blackbeard's ghost: Somali piracy in historical context. Issue 1 (2nd January 2016) - Shirk, Mark
ABSTRACT: Despite renewed interest, one area of piracy studies that can be improved is that of historical comparison. Most studies operate under the belief that piracy is an action similar enough to be compared across time and space. Yet piracy is a socially constructed concept that only has meaning within a narrative and most 'waves' of piracy are characterized by more than one narrative. Thus, comparing all acts of piracy across time and space necessarily means accepting a particular narrative about piracy as true. Much historical-comparative work on piracy compares contemporary piracy to that of the 'golden age' of piracy in the eighteenth century. By focusing on the narratives of both pirates and counter-pirates, piracy in Southeast Asia in the nineteenth century is more comparable to contemporary piracy in the Gulf of Aden. Both 'waves' were characterized by competing narratives of pirates defending local interests vs. the counter-piracy narratives of criminality. This approach highlights similar dynamics in each that can help researchers and policymakers make sense of piracy in the twenty-first century. In particular both 'waves' were characterized by the rise of local political formations built around piracy and the denial of the political content of piracy by counter-pirates.